Mobilni telefoni med varno uporabo in sredstvom nasilja med osnovnošolci - Cvek, Mihaela (visokošolska dela, 2019)
In this doctoral dissertation we discussed mobile phone use among primary school pupils in Slovenia. In the theoretical part we pointed out different aspects of an adolescent's development and the roles of family and peers. We highlighted the place and the role of mobile phones in contemporary society and in adolescents' lives and we pointed out possible dangers and traps of mobile phone use in adolescents. We demonstrated some examples of benign mobile phone use in the educational process and warned about potential traps connected therewith. We placed special attention to different forms of violence among adolescents, especially contemporary technology related violence, and to approaches to its prevention and abolition. The empirical part of the thesis was based on the triangular approach and it represented a combination of quantitative and qualitative pedagogical research. The fundamental finding of the quantitative part of the research, which was being conducted from March to June 2016 and in which 843 pupils from 6th and 9th grades as well as 158 class teachers from primary schools from all statistical regions of Slovenia participated, was that the mobile phones are heavily interwoven into the lives of adolescents. Considering the characteristics and the extent of mobile phone use in pupils, there were some differences concerning the gender and the grade. Girls and pupils from the 9th grade use mobile phones more often than boys and pupils from the 6th grade do. Girls, in comparison to boys, more often state that they associate fear and anxiety with mobile phone use. Mobiles phones represent a status symbol and a means of social interaction as well as exclusion and that is how pupils perceive them. Unlike boys and pupils from the 9th grade, girls and 6th graders more often consider mobile phones as a status symbol and as a means of social interaction or exclusion while, at the same time, they also claim be more aware of harmful mobile phones radiation. The research showed that mobile phones are a means that causes violence and also a means for the execution of violence. Boys are more likely to be offenders and victims in individual acts of violence connected to mobile phones. More precisely, girls and 9th graders tend to be the victims more often than boys and 6th graders, while boys and 9th graders are also the offenders in mobile phone related violence. Furthermore, the research showed that the pupils are more in favour of mobile phone use in the educational process than the teachers are, while teachers are more aware of possible consequences thereof. As the most effective strategy for mobile phone related violence prevention, teachers evaluated consistent reaction in case of an offence in accordance with established rules and as the most effective strategies for mobile phone related violence suppression, they evaluated the following: taking the situation seriously, reacting timely to every sign of violence, talking to the victim and offering them support and help. The qualitative part of the research was based on semi-structured interviews with principals and on school documentation analysis. The basic findings of the interviews with principals of eight primary schools included in this part of this research were that the use of mobile phones during the lessons is forbidden and that they rarely face mobile phone related violence. The principals stressed the bad awareness about possibilities of uncritical mobile phone use among pupils and teachers. As the most effective strategy for violence prevention they see awareness-raising among pupils and as the most effective approach to suppression of related violence they see discussions with pupils. Principals have different visions of prevention and intervention in case of mobile phone related violence. The school documentation analysis showed a considerable non-uniformity and insufficiency in the rules of mobile phone use at schools and in the approaches to noncompliance wit.
Keywords: disertacije; elektromagnetno sevanje; mobilni telefoni; nasilje; odpravljanje; preprečevanje; sredstvo izključevanja; sredstvo povezovanja; statusni simbol; učenci